The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5455/javar.2021.h482
|View full text |Cite
|
Sign up to set email alerts
|

Use and impact of veterinary drugs, antimicrobials, and supplements in fish health management

Abstract: Objective: The study was carried out to investigate the use and impact of veterinary drugs, antimicrobials, and supplements in commercial aquaculture for fish health management measures in three selected areas of Mymensingh, Bangladesh. Materials and Methods: Data collection was conducted through questionnaire interviews with owners of 50 fish farms and 25 drug shop owners from Trishal, Fulpur, Tarakanda, and Sadar Upazila of Mymensingh district. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Some farmers did not use the prescribed treatment doses. A total of 15 antibiotics were identified and farmers were reported with irresponsible and frequent use of such drugs without approval and without knowing their effects on fish health (Faruk et al, 2021). Several issues regarding improper use of aquatic medications, such as lack of information about chemical use, sufficient dosage, form of application, and indiscriminate use of antibiotics have been reported by Hasan et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some farmers did not use the prescribed treatment doses. A total of 15 antibiotics were identified and farmers were reported with irresponsible and frequent use of such drugs without approval and without knowing their effects on fish health (Faruk et al, 2021). Several issues regarding improper use of aquatic medications, such as lack of information about chemical use, sufficient dosage, form of application, and indiscriminate use of antibiotics have been reported by Hasan et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several aqua drugs have been found to be used as oxygen precursors, ammonia reducers, growth promoters, antiparasitics, enzymes, and probiotics to aid digestion and keep the aquatic environment healthy. Antibiotics with six categories of other compounds, including nutritional supplements, disinfectants, saline, ammonia removal, probiotics, and pesticides, were administered by the fish farmers of Mymensingh (Faruk et al, 2021). Previously several authors found very similar outcomes in their research on aqua medicines in Bangladesh (Kawsar et al, 2019;Rahman et., al., 2017;Shamsuzzaman and Biswas, 2012;Chowdhury et al, 2012;Rahman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of aquaculture medicines and chemicals are currently being utilized to prevent production loss as a consequence of this phenomenon (Al-Asif et al, 2021;Chowdhury et al, 2015;Rahman et al, 2019;Ullah et al, 2020). Besides the control of fish health, aqua medicines and chemicals are required for pond preparation, soil and water management, natural aquatic production improvement, feed formulation, and fish growth (Al-Asif et al, 2021;Chowdhury et al, 2015;Faruk et al, 2021;Hossain et al, 2014;Ullah et al, 2020a). Around 1484 aquamedicines generics are being found and commercialized by 100 pharmaceutical businesses over Bangladesh in past decade (Al-Asif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous and uncontrolled intensification of aquaculture creates several health risks of fish such as poor growth, infectious and non-infectious diseases (Hussain et al, 2018). Till now chemotherapy is the only option for prevention and management of aquaculture disease outbreaks which negatively affect the environment and human health (Faruk et al, 2021;Jahan et al, 2021). Hence, in recent years attention is given towards eco-friendly and sustainable methods of aquaculture disease management practices using different plants as immune stimulants (Srichaiyo et al, 2020;Stratev et al, 2018).…”
Section: Introductionmentioning
confidence: 99%